2017
DOI: 10.14196/mjiri.31.34
|View full text |Cite
|
Sign up to set email alerts
|

Comparing minimally supervised home-based and closely supervised gym-based exercise programs in weight reduction and insulin resistance after bariatric surgery: A randomized clinical trial

Abstract: Background: Effectiveness of various exercise protocols in weight reduction after bariatric surgery has not been sufficiently explored in the literature. Thus, in the present study, we aimed at comparing the effect of minimally supervised home-based and closely supervised gym-based exercise programs on weight reduction and insulin resistance after bariatric surgery. Methods: Females undergoing gastric bypass surgery were invited to participate in an exercise program and were randomly allocated into 2 groups u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Despite some weight regain, the proportion of participants with metabolic risk factors remained unchanged in both groups. Several RCTs have aimed at improving weight loss postsurgery [7][8][9][10][11][34][35][36]. The majority of these RCTs have described no differences in weight loss between intervention groups (that received counselling in dietary habits, physical activity, and/or cognitive therapy) and control groups [9,11,34,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite some weight regain, the proportion of participants with metabolic risk factors remained unchanged in both groups. Several RCTs have aimed at improving weight loss postsurgery [7][8][9][10][11][34][35][36]. The majority of these RCTs have described no differences in weight loss between intervention groups (that received counselling in dietary habits, physical activity, and/or cognitive therapy) and control groups [9,11,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…One study found a short-time moderately greater total weight loss in the dietary counselling group that was not maintained beyond the intervention [8]. Some studies show beneficial effect of lifestyle intervention on weight loss start prior to or shortly after surgery [7,10,36] and include only Hispanic Americans [10] or only females [7,36]. Kaviani et al found better weight loss with a closely supervised 20wk exercise programme compared with a minimally supervised exercise programme [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased physical activity has been associated with greater weight loss after bariatric surgery [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Furthermore, close supervision and monitoring of exercise programs support greater weight loss compared to minimally supervised programs [ 85 ]. Egberts et al [ 78 ] in a systematic review of observational studies (on 3852 patients) found a relationship between increased physical exercise (measured by physical activity questionnaires) and weight loss after bariatric surgery (LAGB and RYBG).…”
Section: Physical Activitymentioning
confidence: 99%
“…Bariatric clinics can assist patients in increasing their physical workouts by providing them with visual home exercise routines (DVDs or internet uploaded files) [9]. Home-, outside-, or gym-based physical exercise have been shown to have similar beneficial results on weight loss [10]. Even though all the benefits of exercise are communicated to all pre-and post-operative bariatric surgery patients, there are studies that show non-adherence to physical workout routines by the majority (more than 60%) of patients following bariatric surgery [11].…”
Section: Introductionmentioning
confidence: 99%